Bioremoval of non-steroidal anti-inflammatory drugs by Pseudoxanthomonas sp. DIN-3 isolated from biological activated carbon process. (15th September 2019) - Lu, Zedong; Sun, Wenjun; Li, Chen; Ao, Xiuwei; Yang, Chao; Li, Simiao
Abstract: The presence of non-steroidal anti-inflammatory drugs (NSAIDs) in the environment is an emerging concern owing to their potential threat on aquatic ecosystems and living organisms. To investigate the bioremoval potential of a biological activated carbon (BAC) filter for the removal of NSAIDs, removal of diclofenac (DCF), ibuprofen (IBU), and naproxen (NAP) by biofilms on a bench-scaled BAC column operated for 400 days was studied. The results showed that the BAC column effectively removed the three NSAIDs (>90%). One bacterial strain isolated from the BAC, Pseudoxanthomonas sp. DIN-3, was able to simultaneously remove DCF, IBU, and NAP, which were supplied as the sole carbon source. In 14 days, 23%, 41%, and 39% of DCF, IBU, and NAP (50 μg L −1 ) were bioremoved, respectively, and strain DIN-3 eliminated IBU more rapidly than the other two NSAIDs. If only a single drug was added as the sole carbon source, ignoring the other drugs, the removal ability was overestimated by 5.0–27.0%. More efficient bioremoval was achieved, concomitantly with bacterial growth, via a co-metabolism with acetate, glucose, or methanol. Their intermediates were identified by UPLC-QQQ-MS, and their respective degradation pathways were also proposed. Moreover, based on the complete genome sequence of strain DIN-3, 49 related genes encoding the main enzymes involved in DCF, IBU, and NAP biodegradation were identified, including hemE, lpd, yihx, ligC, pobA, and ligA . These results suggested that Pseudoxanthomonas sp. DIN-3 is a potential degrader of DCF, IBU, and NAP, and to the best of our knowledge, this is the first report that demonstrates the bioremoval of DCF, IBU, and NAP simultaneously by an individual bacterial strain isolated from the environment. However, the bioremoval potential should be evaluated when assessing the applicability of the strain in the environment because of the combined effects of various pharmaceutical contaminants. The obtained results provide a foundation for the use of Pseudoxanthomonas sp. DIN-3 in the bioremoval of polycyclic NSAID-contaminated environments. Graphical abstract: Image 1 Highlights: The removal of diclofenac, ibuprofen, and naproxen in a BAC process was investigated. A bacterium capable of degrading three NSAIDs was firstly isolated from a BAC column. The concomitant presence of the three NSAIDs influenced the biodegradation rates. Chemical and molecular analyses were conducted to evaluate the NSAID degradation pathways.